Brain metabolism after recurrent insulin induced hypoglycaemic episodes: a PET study. Issue 11 (November 1994) - Chabriat, H; Sachon, C; Levasseur, M; Grimaldi, A; Pappata, S; Rougemont, D; Masure, M C; De Recondo, A; Samson, Y
Abstract : Neuropsychological testing was carried out and the rate of oxygen metabolism in the brain was measured by PET in 15 highly selected patients with type 1 diabetes. The aim was to investigate the impact on the brain of hypoglycaemic comas resulting from insulin treatment. No significant difference was found between nine patients with a history of more than 10 hypoglycaemic comas and six others who denied any history of such events. These data suggest that intensified insulin treatment, although increasing the frequency of hypoglycaemic coma, may not always be harmful for the brain. This may be explained by the limited duration of hypoglycaemic coma induced by conventional insulin treatment.